Tracing Neurological Diseases in the Presymptomatic Phase: Insights From Neurofilament Light Chain - Gaetani, Lorenzo; Parnetti, Lucilla; Calabresi, Paolo; Di Filippo, Massimiliano (Frontiers in Neuroscience, 2021)
The identification of neurological diseases in their presymptomatic phase will be a fundamental aim in the coming years. This step is necessary both to optimize early diagnostics and to verify the effectiveness of experimental disease modifying drugs in the early stages of diseases. Among the biomarkers that can detect neurological diseases already in their preclinical phase, neurofilament light chain (NfL) has given the most promising results. Recently, its measurement in serum has enabled the identification of neurodegeneration in diseases such as multiple sclerosis (MS) and Alzheimer’s disease (AD) up to 6–10 years before the onset of symptoms. Similar results have been obtained in conditions such as frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), up to 2 years before clinical onset. Study of the longitudinal dynamics of serum NfL has also revealed interesting aspects of the pathophysiology of these diseases in the preclinical phase. This review sought to discuss these very recent findings on serum NfL in the presymptomatic phase of neurological diseases.